Phraseological Units Containing Similes in Andrić's Devil’s Yard and Their Italian Equivalents - Nermina Čengić (Društvene i Humanističke Studije, 2023)
A simile is a semantic-stylistic figure, very common in literary texts and authors tend to use it to give their text a new, broader, figurative meaning. In the category of simile, there exist simile phrases, that is, a special type of phraseological unit intended to create a more powerful artistic impression. Given the high frequency of use of these lexical elements in Ivo Andrić's literary works, to conclude their structure and use in Bosnian, we will analyze several phraseological units that contain similes, all taken from Andrić's novel Devil’s Yard. We consider it interesting to observe these lexical units contrastively, so in the Italian translation of Devil’s Yard (La Corte del Diavolo) done by Lionello Costantini, we will identify the Italian equivalents of original simile phrases and analyze their characteristics. With this contrastive analysis, we aim to offer an overview of the basic features of special lexical constructions which contain similes, and to make generalizations about the similarities and differences in their structure, meaning and use in the two language systems. The results of this study will also allow us to comment on the intensity of the author's creativity and the skill of the translator to recognize the semantic and stylistic value of these phraseological units and transfer them into the Italian language.